2022
DOI: 10.3390/ma15031032
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Post-Process Heat Treatment Strategy for a Near-α Titanium Base Alloy Produced by Laser Powder Bed Fusion

Abstract: During the last decades, titanium alloys have been of great interest for lightweight applications due to their high strength in combination with a low material density. Current research activities focus on the investigation of near‑α titanium alloys produced by laser powder bed fusion (LPBF). These alloys are known for their superior tensile strength and high creep resistance. This study focuses on the optimization of post‑process heat treatments and the impact on tensile and creep strength of a LPBF produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For instance, in the laser shock peening process, the bending fatigue life of the Ti-6Al-25n-4Zr-2Mo alloy was enhanced by Bhamare et al (2013). The authors concluded that the obtained optimal parametric set form thickness compression yielded an extensive enhancement of the bending fatigue life for the laser powder bed fusion process where the optimization of post-process heat treatments is the concern, Fleißner-Rieger et al (2022) in utilising the Ti-6Al-25n-4Zr-2Mo (Ti-6-2-4-2) alloy concluded as follows. The authors declared that the optimization approach led to the alloy exhibiting optimized ductility and substantial growth of elongation at fracture.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the laser shock peening process, the bending fatigue life of the Ti-6Al-25n-4Zr-2Mo alloy was enhanced by Bhamare et al (2013). The authors concluded that the obtained optimal parametric set form thickness compression yielded an extensive enhancement of the bending fatigue life for the laser powder bed fusion process where the optimization of post-process heat treatments is the concern, Fleißner-Rieger et al (2022) in utilising the Ti-6Al-25n-4Zr-2Mo (Ti-6-2-4-2) alloy concluded as follows. The authors declared that the optimization approach led to the alloy exhibiting optimized ductility and substantial growth of elongation at fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the use of heat treatments to improve the properties of AM components and, depending on the material, could include a series of steps [ 8 , 9 ]. After exploring the literature, it is clear that multistep and single-step post-processing treatments have a place for material enhancement.…”
Section: Introductionmentioning
confidence: 99%